Health financing at district level in Malawi: an analysis of the distribution of funds at two points in time - Borghi, Josephine (Health Policy Plan, 2018)
There is growing attention to tracking country level resource flows to health, but limited evidence on the sub-national allocation of funds. We examined district health financing in Malawi in 2006 and 2011, and equity in the allocation of funding, together with the association between financing and under five and neonatal mortality. We explored the process for receiving and allocating different funding sources at district level. We obtained domestic and external financing data from the Integrated Financial Management Information System (2006–11) and AidData (2000–12) databases. Out-of-pocket payment data came from two rounds of integrated household budget surveys (2005; 2010). Mortality data came from the Multiple Indicator Cluster Survey (2006) and Demographic and Health Survey (2010). We described district level health funding by source, ran correlations between funding and outcomes and generated concentration curves and indices. 41 semi-structured interviews were conducted at the national level and in 10 districts with finance and health managers. Per capita spending from all sources varied substantially across districts and doubled between 2006 and 2011 from 7181 Kwacha to 15 312 Kwacha. In 2011, external funding accounted for 74% of funds, with domestic funding accounting for 19% of expenditure, and out of pocket (OOP) funding accounting for 7%. All funding sources were concentrated among wealthier districts, with OOP being the most pro-rich, followed by domestic expenditure and external funding. Districts with higher levels of domestic and external funding had lower levels of post-neonatal mortality, and those with higher levels of out-of-pocket payments had higher levels of 1–59 month mortality in 2006. There was no association between changes in financing and outcomes. Districts reported delayed receipt of lower-than-budgeted funds, forcing them to scale-down activities and rely on external funding. Governments need to track how resources are allocated sub-nationally to maximize equity and ensure allocations are commensurate to health need.